Somatic parameters of 17 year old soccer players in the older youth category in relation to sports performance - Kutác, P. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
Somatic parameters are included not only in the general structure of sporting performance, but also in the structure of sporting performance in soccer. In light of this structure, higher performance players should have better somatic performance prerequisites, and their somatic parameters should differ from players with lower performance levels. OBJECTIVE: The aim of the study is to assess the somatic parameters of players with different performance levels. METHODS: The research included 90 soccer players in the age of 17 years in three performance categories playing in the junior competition in the Czech Republic. Average age of the individual levels - highest performance 17.61±0.48, middle performance 17.50±0.50, lowest performance 17.50±0.50 years. The following was monitored - basic anthropometric parameters (body weight, body height), somatotype (Heath-Carter), representation of body fat (BF), fat free mass (FFM) and the total body water (TBW). The Tanita 418 MA tetrapolar bioelectrical impedance (BIA) scale was used for the determination of the representation of BF and the TBW. All players were measured at the beginning of the competition period in the same year. All measurements were implemented in the morning hours by the same person with corresponding experience. RESULTS: The average values of somatic parameters measured in the individual performance categories show that we can only consider them to be an indicator of sporting performance up to a particular performance level. The boundary was the middle performance level (teams playing regional competition) as their mean values of the monitored somatic parameters significantly differed from the mean values of players at the lowest performance level (teams playing at the district and municipal levels) but they did not differ when compared with the mean values of the players at the highest performance level (teams playing the top junior league). CONCLUSIONS: From the middle performance level (regional competition), we do not consider the monitored body composition parameters as crucial in terms of individual playing performance.